Isolating active orogenic wedge deformation in the southern Subandes of Bolivia. Issue 8 (25th August 2016) - Weiss, Jonathan R.; Brooks, Benjamin A.; Foster, James H.; Bevis, Michael; Echalar, Arturo; Caccamise, Dana; Heck, Jacob; Kendrick, Eric; Ahlgren, Kevin; Raleigh, David; Smalley, Robert; Vergani, Gustavo
Abstract: A new GPS‐derived surface velocity field for the central Andean backarc permits an assessment of orogenic wedge deformation across the southern Subandes of Bolivia, where recent studies suggest that great earthquakes (> Mw 8) are possible. We find that the backarc is not isolated from the main plate boundary seismic cycle. Rather, signals from subduction zone earthquakes contaminate the velocity field at distances greater than 800 km from the Chile trench. Two new wedge‐crossing velocity profiles, corrected for seasonal and earthquake affects, reveal distinct regions that reflect (1) locking of the main plate boundary across the high Andes, (2) the location of and loading rate at the back of orogenic wedge, and (3) an east flank velocity gradient indicative of décollement locking beneath the Subandes. Modeling of the Subandean portions of the profiles indicates along‐strike variations in the décollement locked width ( WL ) and wedge loading rate; the northern wedge décollement has a WL of ~100 km while accumulating slip at a rate of ~14 mm/yr, whereas the southern wedge has a WL of ~61 km and a slip rate of ~7 mm/yr. When compared to Quaternary estimates of geologic shortening and evidence for Holocene internal wedge deformation, the new GPS‐derived wedge loading rates may indicate that the southern wedge is experiencing a phase of thickening via reactivation of preexisting internal structures. In contrast, we suspect that the northern wedge is undergoing an accretion or widening phase primarily via slip on relatively young thrust‐front faults. Key Points: A new interseismic GPS velocity field for the central Andean backarc includes a correction associated with subduction zone earthquakes The velocity field reveals along‐strike changes in the deformation character of the backarc orogenic wedge The wedge loading rate, décollement locked width, and slipping‐to‐locked transition depth decrease by a factor of ~2 from north to south